Public hospital reforms in China: the perspective of hospital directors - Ju Huang; Tao Dai (BMC, 2019)
Abstract Background To understand the attitudes and opinions of directors of large public hospitals in China on reform policies of public hospital. Method A cross-sectional survey utilizing questionnaires of the Survey of Attitudes to Public Hospital Reform by Directors was conducted in 2014. The respondents were randomly selected in 100 tertiary public hospitals in 62 cities of 31 provinces in China by stratified multistage random cluster sampling method. 178 directors and associate directors working in tertiary public hospitals were involved. Standard descriptive statistics were used to describe and summarize the data. Results The measure of increasing government subsidies ranked first in the list of concerns expressed by responders (N = 149, 83.7%); while implementing clinical pathways ranked lowest in the list of concerns (N = 34, 19.7%). More associate directors (N = 64, 70.3%) were concerned over the measures of removing drug mark-ups than directors (N = 45, 51.7%) (χ2 = 6.49, p = 0.01). In addition, 75.8% of responders were concerned over the policy of salary system reform, while only 14.5% of them were satisfied with their current income level. What's more, more than half responders were concerned over the policy of adjusting pricing policies (N = 127, 71.4%) and removing drug markups (N = 109, 61.2%). Conclusion In healthcare reform, the financial security for the hospitals should be considered as a priority by the policy-makers, without the reform goals cannot be achieved. Thus, an incentive mechanism needs to be established in China to guide the director to focus on the medical quality.